(3CbhGd GdeaSQjf (B:s (3JhLjggG heSGdc GdJhajb HjfgeG (B/s - (3GdMQHj, MSjf Hf Ydjs ((3GdQjGV (B- (3GdSYhOjI (B:s (3OGQ cfhR ETHjdjG ddfTQ hGdJhRjY,s, 2012)
(3jJfGhd cJGH (B((3CbhGd GdeaSQjf JhLjggG heSGdc GdJhajb HjfgG(B) (3hGdPj bGe HJCdjag O(B. (3MSjf Hf Ydj GdMQHj, ehVhY (B((3CbhGd GdeaSQjf(B) (3GdcJGH HMK jSJYQV bVjI ef bVGjG CUhd GdJaSjQ, hgj JhLjg CbhGd GdeaSQjf GdeJYOOI aj eYfi GdBjI, heSGdc GdJhajb Hjf gPg GdCbhGd, hgj bVjI CUjdI aj GdYde(B. (3hbO hab GdHGMK aj YQV GdeSCdI, hHjGf eSGdc JhLjg CbhGd GdeaSQjf hGdLeY HjfgG, ehVMG eG jPcQg HGdCeKdI hGdThGgO(B. s
Keywords: (3CUhd GdJaSjQs